The Relationship between Exercise-Induced Low Back Pain, the Fat Infiltration Rate of Paraspinal Muscles, and Lumbar Sagittal Balance - Masataka Nakamura; Koji Otani; Yota Kaneko; Miho Sekiguchi; Shin-ichi Konno (Spine Surgery and Related Research, 2022)
Introduction: Exercise-induced low back pain (EILBP) is induced during anterior trunk tilting when walking or prolonged standing. In some elderly with chronic LBP, the pain is induced by EILBP. The paraspinal muscles play an important role in supporting the spine; therefore, a dysfunction of back muscles and kyphotic alignment are considered to be associated with EILBP. However, few reports are showing the relationship between EILBP and degenerative muscle changes. This study aimed to clarify the relationship between EILBP, degenerative changes of paraspinal muscles, and spinal alignment in an epidemiological study. Methods: A total of 324 subjects were included in the analysis. The presence of EILBP was determined through a medical interview and physical examination. The subjects underwent lumbar spine magnetic resonance image (MRI) and X-ray. The fat infiltration rate (FIR) of the multifidus, erector spinae, and psoas major were analyzed using MRI. For lumbar sagittal balance, L1 axis S1 distance (LASD) was measured using X-ray images. Multivariate logistic regression analysis was used to analyze the association between the presence of EILBP and FIR or LASD. Results: The prevalence of EILBP was 21% and it increased with age. The subjects with EILBP had statistically higher FIR of the multifidus, erector spinae, and psoas major than those without EILBP. There was a significant association between the presence of EILBP and higher FIR of the erector spinae at L1-2 and L5-S1 (p<0.05). However, there were no significant associations between EILBP and LASD. Conclusions: According to the results in this study, EILBP is not rare and the FIR of the erector spinae is associated with the presence of EILBP.